ChemInform Abstract: Synergistic Gold and Enamine Catalysis: Intermolecular α‐Alkylation of Aldehydes with Allenamides. Issue 26 (June 2016) - Fernandez‐Casado, Jaime; Nelson, Ronald; Mascarenas, Jose L.; Lopez, Fernando
Abstract: Aldehydes are α‐alkylated with allenamides by the combined action of an organocatalyst and a gold complex.